REACTUALIZATION OF THE NON-ALIGNED PRINCIPLE IN INDONESIA’S DIPLOMACY UNDER PRABOWO’S ERA: A CASE STUDY OF THE STATEMENT AT SPIEF 2025 - Paramita Maulidya; Moh. Fathoni Hakim (RADJA PUBLIKA, 2025)
This article analyzes the recontextualization of the Non-Aligned principle in Indonesia’s foreign policy underPresident Prabowo Subianto, using his speech at the St. Petersburg International Economic Forum (SPIEF) 2025as a case study. The focus of this research is how Indonesia’s free and active principle is reinterpreted within thedynamics of a multipolar geopolitical order and growing rivalries among major powers. This study is significant asit demonstrates that the Non-Aligned principle is no longer a mere historical symbol but an adaptive diplomaticstrategy that strengthens Indonesia’s position as an independent and constructive middle power. Employing thetheoretical frameworks of Foreign Policy Analysis (FPA), Middle Power Diplomacy, and Role Theory, the studyadopts a qualitative-descriptive method with a case study approach and applies discourse and content analysistechniques. Data were obtained from the President’s official speech, SPIEF documents, and credible media reports.The findings reveal that President Prabowo’s speech reflects Indonesia’s commitment to active neutralitymaintaining political and military non-alignment while proactively promoting peaceful solutions and cross-bloccooperation. The revitalization of the Non-Aligned principle thus represents Indonesia’s adaptive diplomaticstrategy to preserve sovereignty and global relevance amid contemporary geopolitical shifts.Keywords: Foreign Policy, Global Diplomacy, Middle Power, Non-Aligned, Prabowo